2010
DOI: 10.1007/s10753-010-9214-3
|View full text |Cite
|
Sign up to set email alerts
|

Cryptotanshinone Suppressed Inflammatory Cytokines Secretion in RAW264.7 Macrophages through Inhibition of the NF-κB and MAPK Signaling Pathways

Abstract: Cryptotanshinone (CTS), a major constituent extracted from the medicinal herb Salvia miltiorrhiza Bunge, has well-documented antioxidative and anti-inflammatory effects. In the present study, the pharmacological effects and underlying molecular mechanisms of CTS on lipopolysaccharide (LPS)-induced inflammatory responses were investigated. By enzyme-linked immunosorbent assay, we observed that CTS reduced significantly the production of proinflammatory mediators (tumor necrosis factor-α and interleukin-6) induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
71
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 24 publications
7
71
0
1
Order By: Relevance
“…5B). These results indicated that CTN eventually inhibited NF-κB P65 to translocate to the nucleus and block the expression of its target genes, such as iNOS and COX-2, and our results corroborated that of Tang et al [13] (Fig. 7).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…5B). These results indicated that CTN eventually inhibited NF-κB P65 to translocate to the nucleus and block the expression of its target genes, such as iNOS and COX-2, and our results corroborated that of Tang et al [13] (Fig. 7).…”
Section: Discussionsupporting
confidence: 92%
“…Proinflammatory cytokines upregulate both of COX-2 and iNOS expression via the NF-κB pathway [29]. It has been proven that CTN significantly inhibited the production of proinflammatory cytokines in RAW 264.7 cells after stimulating with LPS [13]. The induction of COX-2 was dramatically suppressed by CTN pretreatment in a dosedependent manner (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[5][6][7] Cryptotanshinone (CPT), an active ingredient isolated from traditional Chinese herb Salvia miltiorrhiza Bunge, demonstrates anti-tumor, anti-inflammation, and antiAlzheimer's disease effects. [8][9][10] A previous study reported that CPT decreases ox-LDL-induced secretion of soluble ICAM-1 (sICAM-1) and soluble VCAM-1 (sVCAM-1) in human umbilical vein endothelial cells (HUVECs), 11 but the underlying mechanisms remain unclear. In this study, the potential mechanisms of CPT inhibiting ox-LDL-induced adhesion molecule expression were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of MAPKs signaling pathways leads to the synthesis and release of pro-inflammatory mediators by activated macrophages during the inflammatory response [6].…”
Section: Introductionmentioning
confidence: 99%